Role of CFTR in Epithelial to Mesenchymal Transition (EMT) by functional genomics - Quaresma, Margarida C (2022)
Mutations in the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) protein cause Cystic Fibrosis (CF), the most common life-shortening monogenic condition in Caucasians. Recent evidence indicates that in addition to being an anion channel CFTR plays a role in other cellular processes, including development, differentiation, and regeneration. Accordingly, reduced/dysfunctional CFTR leads to increased cancer risk. CF was recently suggested to be associated with epithelial-mesenchymal transition (EMT), a latent developmental process, which can be re-activated in fibrosis and cancer. However, it is unknown whether EMT is indeed active in CF, if it is triggered directly by dysfunctional CFTR or by other factors, which pathways bridge CFTR and EMT and how to best study epithelial differentiation in CF. This work was undertaken to clarify these questions. In the first chapter CF native tissues and cells were found to display several signs of active EMT including destructured epithelial proteins/junctions, increased mesenchymal protein levels, and a high proliferation rate. Altogether, the results identified that EMT is intrinsically triggered by absence of functional CFTR through a TWIST1-dependent mechanism. In the second chapter a systems biology approach identified potentially dysregulated EMT signalling in CF (including the Hippo, Wnt, TGF-β, p53 and MYC pathways), integrated by YAP1 and TEAD4. Thus, putative proteins and pathways mediating EMT and fibrosis in CF were identified with potential therapeutic outcomes to both CF and cancer. In the third chapter immortalized basal cell models BCi-NS1.1 and BCi-CF1.1 (models of epithelial cell differentiation expressing wt- and F508del-CFTR) were characterized regarding their cellular junctions and differentiation status. Preliminary data pointed to F508del-CFTR impairing formation of several cell junctions and resulting in loss of stemness. Altogether these findings suggest that CFTR plays a direct role in EMT protection and proper epithelial cell differentiation and that its dysfunction promotes activation of detrimental signalling pathways and phenotypes.